Repurposing Drugs for Synergistic Combination Therapies to Counteract Monkeypox Virus Tecovirimat Resistance - Haydar Witwit; Beatrice Cubitt; Roaa Khafaji; Esteban M. Castro; Miguel Goicoechea; Maria M. Lorenzo; Rafael Blasco; Luis Martinez-Sobrido; Juan C. de la Torre (Viruses)
The ongoing monkeypox (mpox) disease outbreak has spread to multiple countries in Central Africa and evidence indicates it is driven by a more virulent clade I monkeypox virus (MPXV) strain than the clade II strain associated with the 2022 global mpox outbreak, which led the WHO to declare this mpox outbreak a public health emergency of international concern. The FDA-approved small molecule antiviral tecovirimat (TPOXX) is recommended to treat mpox cases with severe symptoms, but the limited efficacy of TPOXX and the emergence of TPOXX resistant MPXV variants has challenged this medical practice of care and highlighted the urgent need for alternative therapeutic strategies. In this study we have used vaccinia virus (VACV) as a surrogate of MPXV to assess the antiviral efficacy of combination therapy of TPOXX together with mycophenolate mofetil (MMF), an FDA-approved immunosuppressive agent that we have shown to inhibit VACV and MPXV, or the N-myristoyltransferase (NMT) inhibitor IMP-1088. Both MMF and IMP-1088 drugs exhibited strong dose-dependent antiviral activity against VACV and mpox, and potent synergistic effects in conjunction with TPOXX. Our findings support combination therapy of direct-acting (TPOXX) and host-targeted (MMF and IMP-1088) antivirals as a promising approach to treat mpox and prevent the emergence and spread of TPOXX-resistant MPXV variants.